Arsenic Accumulation in Common Vegetables from Irrigation - Islam, M. N.; Das, B. K.; Huque, M. E. (Journal of Scientific Research, 2012)
Arsenic-accumulation pattern in eight types of vegetables commonly found in Bangladesh were studied using successive irrigation/harvesting technique. The study also included to find the threshold amount of arsenic that leads to exceed the maximum permissible limit (MPL) in those vegetables and several water-soil-plant arsenic concentration models. Total arsenic concentrations were measured by Hydride GenerationAtomic Absorption Spectroscopy (HG-AAS) technique. Arsenic-accumulation decreased in the order: Arum > Arum leaf > Amaranth > Brinjal > Radish > Indian Spinach > Carrot > Okra. A single harvesting of 10 irrigations with water (3.0 L/irrigation) having arsenic concentrations of ?0.45 mg L-1 to 0.071 m2 area (equivalent to 1.89 kg As ha-1) exceeded the MPL in vegetables (1 mg kg-1, wet weight). The concentration of accumulated arsenic in the vegetables increased linearly with time and exponentially with successive harvesting. Regression analyses showed that arsenic concentration in vegetables was positively correlated with that of irrigation water and soil (r = 0.796 for both cases). © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10494 J. Sci. Res. 4 (3), 675-688 (2012)